Mexico: 30 years of neoliberal paradigm - V. M. Davydov (Ибероамериканские тетради)
Interview with Vladimir Mikhailovich Davydov, Doctor of Economics, Corresponding Member of the Russian Academy of Sciences, Scientific Director of the Institute of Latin America of the Russian Academy of Sciences, Director of the Institute of Latin America of the Russian Academy of Sciences (1995-2017). Being one of the leading specialists in Latin American studies in Russia, Dr. Davydov is the author of more than 350 research papers. His works made a huge contribution to the study of socio-economic and political processes taking place in Latin America, as well as to the development of Iberoamericanism in Russia.The interview was conducted by: A.A. Habarta.